2014
DOI: 10.1128/jcm.03047-13
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genotypic Characterization of Canadian Clinical Isolates of Vibrio parahaemolyticus Collected from 2000 to 2009

Abstract: e Vibrio parahaemolyticus is the leading bacterial cause of food-borne illness due to the consumption of contaminated seafood. The aim of the present study was to determine the population of its subtypes and establish a better understanding of the various types of V. parahaemolyticus strains that are causing human illness in Canada. The subtypes for 100 human clinical isolates of V. parahaemolyticus collected between 2000 and 2009 were determined by performing serotyping, ribotyping, pulsed-field gel electroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 33 publications
2
60
0
Order By: Relevance
“…Confirmation could be done by additional genotyping, such as for the flp locus ( Fig. 2 and Table 1) (16), by application of one of the other primer sets for prp (Table 1), through other typing methods, including PFGE and serotyping (15), by four-or seven-gene MLST (17,18,21,30) (Fig. 1), or, when resources are available, by whole-genome sequencing and phylogeny (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Confirmation could be done by additional genotyping, such as for the flp locus ( Fig. 2 and Table 1) (16), by application of one of the other primer sets for prp (Table 1), through other typing methods, including PFGE and serotyping (15), by four-or seven-gene MLST (17,18,21,30) (Fig. 1), or, when resources are available, by whole-genome sequencing and phylogeny (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few virulence markers are known and routinely applied to pathogen identification, including the tdh and trh hemolysin genes, but these do not detect all pathogens. Indeed, Ͼ10% of infections in North America are apparently caused by strains that lack these genes, whose prevalence among nonpathogens and other Vibrio species is not known (10)(11)(12)(13)(14)(15). The detection of a combination of traits or markers that can identify pathogen lineages of most concern, along with quickly and affordably identifying virulence traits, could improve the reliability of pathogen discrimination, identification, and surveillance.…”
mentioning
confidence: 99%
“…Recent studies have reported the isolation of strains that lack both tdh and trh (tdh-and trh-negative strains) from clinical samples (22)(23)(24)(25)(26)(27). However, the ability of tdh-and trh-negative strains to independently cause clinical illness is still controversial.…”
mentioning
confidence: 99%
“…Among the infections associated with the genus Vibrio, the majority was caused by V. parahaemolyticus (Crim et al, 2014). While most foodborne pathogens (i.e., Listeria, Campylobacter, and Escherichia coli O157) have shown a decrease in incidence from 1998 to 2008, V. parahaemolyticus has increased 47% within this time period (Banerjee et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Underreporting can be attributed by the lack of awareness of the disease, the self-limiting nature of the infection, and the lack of urgency to visit physicians (Banerjee et al, 2014).…”
Section: Introductionmentioning
confidence: 99%